PROBLEMATIKA PEMBELAJARAN DARING PADA MATA PELAJARAN GEOGRAFI DI SMAN 1 PADANG GANTING,KECAMATAN PADANG GANTING,KABUPATEN TANAH DATAR - Uci Susanti (JURNAL BUANA, 2022)
The objective of this study is to explain and explain the problems of online learning. (Understanding IT, Data Network Learning Facilities / Signal Network Quota) in Geography at SMA Negeri 1 Padang Ganting, Padang Ganting District, Tanah Datar Regency. This research is a qualitative research method. Field volunteers were descriptive and data was obtained through observations, interviews and documentation. This research was conducted from March to April 2021. The analysis of the data revealed that the typical online learning problems that students and teachers felt were 1) problems understanding IT, 2) learning facilities, 3) data networks / quotas, and 4. Network / signal problem